A 5‐week randomized clinical evaluation of a novel electric toothbrush head with regular and tapered bristles versus a manual toothbrush for reduction of gingivitis and plaque. Issue 2 (19th December 2018) - Ccahuana‐Vasquez, Renzo Alberto; Adam, Ralf; Conde, Erinn; Grender, Julie M.; Cunningham, Pamela; Goyal, C. Ram; Qaqish, Jimmy
Abstract: Objective: To evaluate the efficacy of an oscillating‐rotating (O‐R) electric rechargeable toothbrush with a novel round brush head comprised of regular and tapered bristles in reducing plaque and gingivitis versus a manual toothbrush. Methods: This was a randomized, examiner‐blind, parallel group, five‐week study. Participants with mild‐to‐moderate plaque and gingivitis received an oral examination and were evaluated for baseline plaque (Rustogi Modified Navy Index), gingivitis (Modified Gingival Index) and gingival bleeding (Gingival Bleeding Index). Qualifying participants were randomly assigned to the novel Oral‐B sensitive brush head (EB60) on an Oral‐B Vitality O‐R handle (D12) or an ADA manual toothbrush. Participants brushed twice daily with the assigned brush and a standard fluoride dentifrice for 5 weeks before returning for an oral examination and plaque and gingivitis evaluations. Results: A total of 150 participants were randomized to treatment and completed the study (mean age = 45.7 years). Both brushes demonstrated a statistically significant reduction in number of bleeding sites versus baseline ( P < 0.001). At Week 5, the number of bleeding sites was reduced from baseline by 11.15 (52.2%) for the O‐R brush and 5.04 (23.6%) for the manual brush. The treatment difference was statistically significant ( P < 0.001). Significant reductions versus baseline ( P < 0.001) were also seen for both brushes for MGI, GBI and Rustogi plaque measures (whole mouth, gingival margin and proximal), but the O‐R brush produced significantly greater reductions versus the manual brush ( P < 0.001). Conclusion: The O‐R handle and round brush head with tapered and regular bristles produced greater plaque and gingivitis reductions than the manual brush.